PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM), RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi Empiris Perusahaan Food And Beverage Yang Terdaftar Di BEI 2012-2014) - Istianah, 13.05.62.0018; Wahjudi, Djoko (Students Journal of Accounting and Banking, 2016)
This study examined the effect of current ratio (CR), debt to equity ratio (DER), net profit margin (NPM), return on assets (ROA) and return on equity (ROE) to the stock price. This research was carried out on food and beverage companies listed on stock exchanges in Indonesia. The sampling method using purposive sampling the study period of 2012 through 2014. The relationship and influence between the variables described by using multiple linear regression analysis. The results showed that the current ratio(CR) positive effect on stock prices. While the debt-to-equity ratio (DER), net profit margin (NPM), return on assets (ROA) and return on equity (ROE) had no significant effect on stock prices.Keywords: Current Ratio (CR), Debt To Equity Ratio (DER), Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Stock Prices